2013
DOI: 10.1074/jbc.m113.458265
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Activity of Lactate Dehydrogenases from Four Lactic Acid Bacteria

Abstract: Background: Lactate dehydrogenases (LDHs) are key metabolic enzymes in lactic acid bacteria (LAB). Results: The effects of fructose 1,6-bisphosphate, phosphate, pH, and ionic strength on enzyme activity differ for six LDHs from four LAB. Conclusion:The regulation of LDH activity differs among LAB. Significance: These results have implications for understanding enzyme evolutionary adaptation, for quantitative comparative modeling, and for biotechnological application of LAB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 32 publications
1
41
0
Order By: Relevance
“…However, the kinetic parameters of the Ec. faecalis LDH‐2 [27] are obviously different from those of the Ec. mundtii LDH‐2 and the Lc.…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…However, the kinetic parameters of the Ec. faecalis LDH‐2 [27] are obviously different from those of the Ec. mundtii LDH‐2 and the Lc.…”
Section: Resultsmentioning
confidence: 68%
“…On the other hand, deletion of ldh‐ 2 kept the homolactic fermentation, suggesting that LDH‐2 plays only a minor role in the lactate production. Kinetic study showed that the K m values of LDH‐2 for both pyruvate and NADH are larger than those of LDH‐1, indicating the minor role in lactate production [27].…”
Section: Resultsmentioning
confidence: 96%
“…e ability of E. faecalis to produce L(+)-lactic acid from glucose or lactose by homolactic fermentation was earlier demonstrated in the literature. Lactate is generated through pyruvate reduction and two enzymes are involved in this reaction; the cytosolic NAD + -dependent L-(+)-lactate dehydrogenases: ldh-1 and ldh-2 [32].…”
Section: Effect Of Culture Media and Scale-up On Lactic Acid And Biommentioning
confidence: 99%
“…The bacterial LdhLs (NAD-dependent LdhL) include an FBPdependent LdhL and an FBP-independent LdhL (30), and LdhL1 of E. faecalis is the FBP-dependent LdhL (31). The activity of FBPdependent Ldh is highly dependent on FBP produced from fructose 6-phosphate by 6-phosphofructokinase (Pfk) using ATP in glycolysis (31); however FBP is not produced in the glycerol metabolic pathway because glycerol is converted to DHAP and then enters glycolysis (9).…”
Section: Discussionmentioning
confidence: 99%